(untitled) (Research, Society and Development, 2021)
In Brazil, the reality experienced by homeless people is marked by great social inequality. The uncertainty generated by living on the streets is due to constant exposure to dangers. It is a heterogeneous group, linked to extreme poverty, including pregnant women. The objective of this research is to characterize the vulnerabilities experienced by pregnant women living on the streets. It is a qualitative descriptive research of an integrative review; whose aspects facilitate the identification of relevant results. The collection of information for bibliographic research was done through the databases of the Virtual Health Library (VHL), accessed through the Nursing Database (BDENF); Virtual Electronic Scientific Library (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Google scholar. From this research it is expected to contribute and expand the debate on the difficulties of pregnant women on the street, the obstacles faced by the multiprofessional teams of the street office. The search found 16 articles on the topic, published between 2015 and 2019. These were divided into three categories: pregnant women who use drugs, their daily lives and the importance of prenatal care, and access to health for this group. It was concluded that the little knowledge of health professionals, about the difficulties faced by these pregnant women, interferes in the segment and adherence to prenatal care. Building a relationship with these pregnant women is essential, as it helps to improve the service that serves this audience.